2006
DOI: 10.1074/jbc.m512540200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Sequestration of the Recycling Compartment by Classical Protein Kinase C

Abstract: It has been previously shown that upon sustained stimulation (30 -60 min) with phorbol esters, protein kinase C (PKC) ␣ and ␤II become sequestered in a juxtanuclear region, the pericentrion. The activation of PKC also results in sequestration of transferrin, suggesting a role for PKC in regulating endocytosis and sequestration of recycling components. In this work we characterize the pericentrion as a PKC-dependent subset of the recycling compartment. We demonstrate that upon sustained stimulation of PKC, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 43 publications
6
65
0
Order By: Relevance
“…Recent studies have identified a novel translocation of PKC to a juxtanuclear compartment, the pericentrion, which is distinct from the Golgi complex but epicentered on the centrosome. Sustained activation of PKC also results in sequestration of plasma membrane lipids and proteins to the same compartment (44). Possibly, PKC contributes to cell protection from complement by facili- tating translocation of C5b-9 from the plasma membrane to the pericentrion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified a novel translocation of PKC to a juxtanuclear compartment, the pericentrion, which is distinct from the Golgi complex but epicentered on the centrosome. Sustained activation of PKC also results in sequestration of plasma membrane lipids and proteins to the same compartment (44). Possibly, PKC contributes to cell protection from complement by facili- tating translocation of C5b-9 from the plasma membrane to the pericentrion.…”
Section: Discussionmentioning
confidence: 99%
“…Activity-A previous study implicated PKC in agonist-induced 5-HT 2A R internalization (20), and our work has established a critical role for cPKC in the sequestration of recycling molecules into a subset of endosomes in the perinuclear region (6,7). In addition, it was demonstrated previously that sustained activation of cPKC by PMA not only caused sequestration of recycling components but also led to a concomitant translocation of cPKC␣ and -␤II but not -␤I into the pericentrion (8).…”
Section: Sequestration Of 5-ht 2a Receptors Coincides With Sequestratmentioning
confidence: 98%
“…Evidence from our studies pointed that both the constitutive and the PKC-modulated OAT1 internalization occurred partly through a dynamin-and clathrin-dependent pathway. Indeed, treatment of OAT1-expressing cells with ConA, depletion of K ϩ from the cells, or transfection of dominant negative mutants of dynamin-2 into the cells, all of which blocked clathrin-dependent pathway (42)(43)(44)(45), significantly blocked OAT1 internalization (Figs. 8 -10).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether OAT1 internalizes via clathrin-dependent pathway, the constitutive and PKC-modulated OAT1 internalization were determined under the manipulations that specifically block clathrin-dependent internalization (42)(43)(44)(45): (i) treatment of the cells with concanavalin A (ConA) (Fig. 8a, top panel and Fig.…”
Section: Characterization Of Oat1 In Cos-7mentioning
confidence: 99%